Effects of Binahong Leaf Decoction on Perineal Laceration Healing in Postpartum Women - Himalaya, Dara; Maryani, Deni (Global Medical & Health Communication (GMHC), 2022)
A perineal laceration is a wound of the skin and muscular area between the vaginal and anal introitus caused by a labor tear. Perineal lacerations might occur in sudden and rapid removal of the fetus' head, excessive fetus size, and the inability of the pelvic muscles and soft tissues to accommodate the fetus's birth. One of the empirical non-pharmacology approaches to this study sought to understand the effect of binahong (Anredera cordifolia (Tenore) Steenis) leaf decoction on peritoneal wound healing in postpartum women. This is a quasi-experimental post-test-only control group study on 30 postpartum women treated in 15 private midwife practices in Bengkulu city from 10 November to 10 December 2022 who met the inclusion criteria. Subjects were sampled using the accidental sampling technique and were randomly divided into two groups. Wound healing was assessed using the REEDA scale, and the results were analyzed statistically using the Mann-Whitney or Wilcoxon test and the chi-square test. The study's results showed that Hb, age, and the number of children's influenced perineal wound healing. The average number of days for wound healing in the treatment group was six days. For a control group that used povidone-iodine 10% was eight days. It is concluded that there is an effect of decoction of the leaves of binahong (Anredera cordifolia (Tenore) Steenis) on the healing of peritoneal wounds in postpartum women.